New Features of the Process of National Identity Understanding in the Formation of the Global Information Space (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article discusses the issues of studying the essence, characteristics, formation factors, and social significance of the phenomenon of national identity in the context of today's global information space and the “network society” that is being formed under its influence.